2017
DOI: 10.1016/j.physe.2017.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-confined Stark effect in band-inverted junctions

Abstract: Topological phases of matter are often characterized by interface states, which were already known to occur at the boundary of a band-inverted junction in semiconductor heterostructures. In IV-VI compounds such interface states are properly described by a two-band model, predicting the appearance of a Dirac cone in single junctions. We study the quantum-confined Stark effect of interface states due to an electric field perpendicular to a band-inverted junction. We find a closed expression to obtain the interfa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Moreover, we have observed that the reduction in the velocity squares with the applied field, a feature that was recently found also in the case of static fields. 10,11 Our study provides a more promising experimental set up in order to obtain an anisotropic renormalization of the velocity based on a time-periodic driving and no need for a magnetic field. 13 All of our findings should be straightforwardly probed by means of time-and angle-resolved photoemission spectroscopy, as discussed in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we have observed that the reduction in the velocity squares with the applied field, a feature that was recently found also in the case of static fields. 10,11 Our study provides a more promising experimental set up in order to obtain an anisotropic renormalization of the velocity based on a time-periodic driving and no need for a magnetic field. 13 All of our findings should be straightforwardly probed by means of time-and angle-resolved photoemission spectroscopy, as discussed in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier works in Dirac materials have proven that a renormalization of the Fermi velocity of the surface states occurs in the presence of a perpendicular electric field. 34,35 Therefore, we expect similar effects in WSMs and DSMs. We approach the problem in two ways: i) by way of perturbation theory (PT) to obtain analytic results and ii) by performing numerical calculations based on the Python package Kwant.…”
Section: Electric Fieldmentioning
confidence: 78%
“…All these topological states of matter were already encountered in a series of seminal papers by Volkov and Pankratov in the 1980s [80][81][82][83][84][85]. Remarkably, these states can be reshaped by means of external electric and magnetic fields [86][87][88][89] and doping [90,91]. Another example of these such states can be found in HgTe.…”
Section: Topological Insulator Nanowiresmentioning
confidence: 99%